(untitled) (Journal of Economic Research & Business Administration, 2015)
The problem of the analysis of data of science, education and innovative activity is a complex and complex challenge, and to conduct the researches connected with these spheres of human activity, it is possible in the various ways, with use of different techniques and different methodical approaches.